2023
DOI: 10.1111/1755-6724.15060
|View full text |Cite
|
Sign up to set email alerts
|

Early Cretaceous Thrust and Nappe Tectonics in North Qilian Shan, Northern Tibetan Plateau: Evidence from Field Mapping, Geochronology, and Deep Structural Analysis

Abstract: The North Qilian Shan fold and thrust belt, located at the northern Tibetan Plateau and southern margin of the Hexi Corridor, is a key tectonic unit to decode the formation and expansion of the plateau. Previous studies emphasize the Cenozoic deformation due to the far‐field response to the Indo‐Asian collision, but the Mesozoic deformations are poorly constrained in this area. We conducted detailed field mapping, structural analysis, geochronology, and structural interpretation of deep seismic reflectional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…(2022), Han et al. (2023), and this study. (a) Late Middle Jurassic–Early Cretaceous thrusting, nappe emplacement, crustal shortening, and foreland‐like basin development in the Beishan fold‐thrust belt to the NE Tibetan region.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…(2022), Han et al. (2023), and this study. (a) Late Middle Jurassic–Early Cretaceous thrusting, nappe emplacement, crustal shortening, and foreland‐like basin development in the Beishan fold‐thrust belt to the NE Tibetan region.…”
Section: Discussionsupporting
confidence: 68%
“…The structural and kinematic evolution of the late Mesozoic Beishan fold‐thrust belt, which was minimally overprinted in the Cenozoic, has important implication for understanding the pre‐Cenozoic uplift and deformation history of the NE Tibetan Plateau. For example, Cenozoic deformation strongly overprinted the earlier tectonic history of the Qilian Shan (Jolivet et al., 2001; B. Li et al., 2019, 2021; Yin et al., 2008; Zuza et al., 2016, 2018), but there is evidence for Early Cretaceous contractional deformation (X. H. Chen et al., 2019a, 2019b; Han et al., 2023; Y. Wang et al., 2022; Wu et al., 2011) that temporally and spatially correlates with the development of the Beishan fold‐thrust belt (Figures 14 and 15a). The uplifted Beishan Range and Qilian Shan provided the main sources of Lower Cretaceous proximal deposits in the Yumen Basin (Cheng et al., 2019) (Figure 15a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our structural analysis also indicates that there was a compressional event prior to the Late Cenozoic North Qilian uplift, which led to the initial tilting and duplication of Devonian to Jurassic units in our research area. Previous studies have identified three compressional events that could explain this deformation: a Late Triassic to Early Jurassic event and an Early Cretaceous event (Cheng et al, 2019;Han et al, 2023;Jolivet et al, 2001;Tong et al, 2020;, or a possible Eocene-Oligocene early event that defined the early extent of the Tibetan Plateau (Clark, 2012;Wu et al, 2021;Zuza et al, 2019Zuza et al, , 2020. The unconformity between Oligocene and Devonian to Jurassic units supports that this event took place prior to the Oligocene; omission of Jurassic units in Yaoquan and Dahuanggou areas may favor a Late Triassic to Early Jurassic age for this event.…”
Section: Spatial and Temporal Relationship Of The Fold-and-thrust Beltmentioning
confidence: 83%
“…Wang et al, 2018). Later, during the Early Cretaceous, recent studies on sedimentology, thermochronology, and seismic reflection data suggest another compressional event characterized by NW-striking thrusting and folding (Han et al, 2023;, quickly followed by N-S extension (S. Chen et al, 2014;Cheng et al, 2019;Jolivet et al, 2001;Pan et al, 2013;Vincent & Allen, 1999;Yin et al, 2008;Zuza et al, 2016). These Cretaceous events are interpreted as a result of collision of the Lhasa/Qiangtang terrane and subsequent orogenic collapse.…”
Section: Tectonicsmentioning
confidence: 99%